Koncepcja odpowiedzialności społecznej firm farmaceutycznych - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2010)
The burden of social responsibility is on the pharmaceutical industry. It is producing drugs and medical equipment which have to fulfill high quality standards, because they are very important from society point of view. The main business activity of pharmaceutical companies can be assessed as doing something good. However, a lot of drug producers are also involved in other ways of working for public wellness. There are using a great range of the instruments and programs to manage the corporate social responsibility. The article describes the results of 31 in-depth interviews with the pharmaceutical sales representatives conducted between the June – November 2007. It shows what problems can be created during organizing: charity action, white Sundays, conferences for physicians and other pro bono events. It explains how such actions can meet with public opinion accusations. The main aim of this paper is to answer the questions: What are the advantages of realizing CSR for pharmaceutical companies? Is it true that this conception is used as a marketing tool by drug producers? What the pharmaceutical sales representatives think about charity actions that are conducted in their companies?